The cag PAI is intact and functional but HP0521 varies significantly in Helicobacter pylori isolates from Malaysia and Singapore - Schmidt, H.M.A.; Andres, S.; Nilsson, C.; Kovach, Z.; Kaakoush, N.O.; Engstrand, L.; Goh, K.L.; Fock, K.M.; Forman, D.; Mitchell, H. (Springer Verlag (Germany), 2010)
Helicobacter pylori-related disease is at least partially attributable to the genotype of the infecting strain, particularly the presence of specific virulence factors. We investigated the prevalence of a novel combination of H. pylori virulence factors, including the cag pathogenicity island (PAI), and their association with severe disease in isolates from the three major ethnicities in Malaysia and Singapore, and evaluated whether the cag PAI was intact and functional in vitro. Polymerase chain reaction (PCR) was used to detect dupA, cagA, cagE, cagT, cagL and babA, and to type vacA, the EPIYA motifs, HP0521 alleles and oipA ON status in 159 H. pylori clinical isolates. Twenty-two strains were investigated for IL-8 induction and CagA translocation in vitro. The prevalence of cagA, cagE, cagL, cagT, babA, oipA ON and vacA s1 and i1 was > 85%, irrespective of the disease state or ethnicity. The prevalence of dupA and the predominant HP0521 allele and EPIYA motif varied significantly with ethnicity (p < 0.05). A high prevalence of an intact cag PAI was found in all ethnic groups; however, no association was observed between any virulence factor and disease state. The novel association between the HP0521 alleles, EPIYA motifs and host ethnicity indicates that further studies to determine the function of this gene are important.